2019
DOI: 10.1021/jacs.9b06126
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonyl Fluoride Synthesis through Electrochemical Oxidative Coupling of Thiols and Potassium Fluoride

Abstract: Sulfonyl fluorides are valuable synthetic motifs for a variety of applications, among which sulfur(VI) fluoride exchange-based “click chemistry” is currently the most prominent. Consequently, the development of novel and efficient synthetic methods to access these functional groups is of great interest. Herein, we report a mild and environmentally benign electrochemical approach to prepare sulfonyl fluorides using thiols or disulfides, as widely available starting materials, in combination with KF, as an inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 39 publications
2
110
0
Order By: Relevance
“…Next, we investigated the influence of the fluoride source on the reaction outcome ( Table 3). As shown in our previous work [15], the reaction worked well with alkali fluorides but also with Selectfluor. The use of Selectfluor was not further considered due to low atom efficiency and its higher price compared to alkali fluorides.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Next, we investigated the influence of the fluoride source on the reaction outcome ( Table 3). As shown in our previous work [15], the reaction worked well with alkali fluorides but also with Selectfluor. The use of Selectfluor was not further considered due to low atom efficiency and its higher price compared to alkali fluorides.…”
Section: Resultssupporting
confidence: 78%
“…It is possible that pyridine functions either as an electron mediator [23] or a as phase transfer catalyst. From our mechanistic investigations [15], we believe that at least pyridine functions partly as a phase transfer catalyst (Table 4). Screening the concentration of pyridine, we found that the best results were obtained with 0.6-0.7 M pyridine ( Table 4, Entries 6 and 9).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Unsurprisingly, these latter two reports focus exclusively on planar arene and heteroarene substrates. A recent report has described the electrochemical coupling of thiols and potassium fluoride as a route to sulfonyl fluorides …”
Section: Methodsmentioning
confidence: 99%